Beliefs and intention in choosing agriculture as a career among academic and technical schools' students - Abd Wahid, Nur Husna (2010)
The study involved 698 form four agricultural students in academic and technical schools in four zones of peninsular Malaysia (North zone, Central zone, South zone, and East zone). The respondents consisted of students from four groups. First were students who enrolled in agriculture science subjects in academic schools. Second were students who enrolled in agriculture vocational subjects in academic schools. Third were students who enrolled in agriculture subjects in technical schools and the fourth group were students who enrolled in agriculture vocational subjects in technical school. The study aims to examine students’ beliefs and intention towards choosing agriculture as a career. The variables studied were attitudinal beliefs, normative beliefs, and intentions towards choosing agriculture as a career. The instrument employed in this study was adapted from the instrument used in the studies which also measures people’s belief and intention. Stratified sampling was applied to ensure that a representative sample from the population of agriculture students was obtained in this study. The response rate for this study was 87.3 %. The findings indicate that attitudinal belief for construct ‘contribution to other people or organization’ shows the highest mean value of belief among agriculture students. Findings also indicate that mothers and agricultural teachers were among the people who strongly influenced students towards choosing agriculture as a career. Overall, agriculture students showed a high level of intention towards choosing agriculture as a career. However, ANOVA confirms that demographic characteristic namely types of agriculture subjects enrolled were found to have significant difference in students’ beliefs [F (3,692, P<.05) = 20.88] and intentions [F (3,694, P<.05) = 14.36] towards choosing agriculture as a career. In addition, Correlation test indicates that attitudinal belief for construct ‘perception of other people close to students’, demonstrated a very high relationship with students’ intention of choosing agriculture as a career.